Magnitude of Domestic Violence and Associated Factors among Pregnant Women in Hulet Ejju Enessie District, Northwest Ethiopia - Tenaw Yimer; Tesfaye Gobena; Gudina Egata; Habtamu Mellie (Hindawi Limited, 2014)
Introduction. Domestic violence during pregnancy is one of the barriers to achieve MDG 3 due to its adverse health consequences. Comparable population-based data on the problem are lacking as existing literatures differ in time periods explored. Such discrepancies among study findings indicate the importance of site specific studies, especially in rural parts of Ethiopia, where little is known about the problem. Objective. The aim of this study was to assess the magnitude of domestic violence and its associated factors among pregnant women in Hulet Ejju Enessie district, northwest Ethiopia. Methods and Materials. Quantitative community based cross-sectional study was carried out from January 1 to 31, 2014. A total of 425 randomly selected pregnant women were involved in the study. A standard WHO multicountry study on women's health and domestic violence questionnaire were used for data collection. Four trained female data collectors were involved. Odds ratio with 95% CI was estimated to identify factors associated with domestic violence during pregnancy using multivariate logistic regression. Statistical significance was declared at P value ≤0.05. Results. The prevalence of domestic violence during current pregnancy was 32.2%. The prevalence of psychological, sexual, and physical violence was 24.9%, 14.8%, and 11.3%, respectively. Married women at the age of ≤15 years were about four times (AOR = 4.2, 95% CI 1.9-9.0) more likely to experience domestic violence during pregnancy than their counterparts. Meanwhile, interparental exposure to domestic violence during childhood (AOR = 2.3, 95% CI 1.1-4.8), having frequently drinker partner (AOR = 3.4, 95% CI 1.6-7.4), and undesired pregnancy by partner (AOR = 6.2, 95% CI 3.2-12.1) were the main significant factors that increase risk of domestic violence during pregnancy. Conclusion and Recommendation. In this study, the prevalence of domestic violence during current pregnancy is high which may lead to a serious health consequence both on the mothers and on their foetuses. Thus, targeted efforts should be made by all concerned stakeholders to reduce the problem in the study area.